Mycobacterium avium complex olecranon bursitis resolves without antimicrobials or surgical intervention: A case report and review of the literature. Issue 2 (2015) - Working, Selene; Tyser, Andrew; Levy, Dana
Abstract Introduction Nontuberculous mycobacteria are an uncommon cause of septic olecranon bursitis, though cases have increasingly been described in both immunocompromised and immunocompetent hosts. Guidelines recommend a combination of surgical resection and antimicrobials for treatment. This case is the first reported case of nontuberculous mycobacterial olecranon bursitis that resolved without medical or surgical intervention. Case presentation A 67-year-old female developed a painless, fluctuant swelling of the olecranon bursa following blunt trauma to the elbow. Due to persistent bursal swelling, she underwent three separate therapeutic bursal aspirations, two involving intrabursal steroid injection. After the third aspiration, the bursa became erythematous and severely swollen, and bursal fluid grew Mycobacterium avium complex. Triple-drug antimycobacterial therapy was initiated, but discontinued abruptly due to a rash. Surgery was not performed. The patient was observed off antimicrobials, and gradually clinically improved with a compressive dressing. By 14 months after initial presentation, clinical exam revealed complete resolution of the previously erythematous bursal mass. Discussion This is the first reported case of nontuberculous mycobacterial olecranon bursitis managed successfully without surgery or antimicrobials. Musculoskeletal nontuberculous mycobacterial infections are challenging given the lack of clinical data about optimal duration and choice of antimicrobials or the role of surgery. Additionally, the potential toxicity and drug interactions of antimycobacterials are not insignificant and warrant close monitoring if treatment is pursued. Conclusion This case raises an important clinical question of whether close observation off antimicrobials is appropriate in select cases of immunocompetent patients with localized atypical mycobacterial disease of soft tissue and skeletal structures.